Complete chloroplast genome sequences of the medicinal plant Piper hancei. Issue 9 (2nd September 2021) - Zhang, Lvshui; Hu, Xiaokang; Liu, Mu
Abstract: Chloroplast genome sequences have been used in phylogenetic and population genetics studies. Here, we assembled the chloroplast genome of Piper hancei Maxim. that is a traditional Chinese medicine. The genome length was 161, 476 bp and included a pair of inverted repeats of 27, 058 bp, a large single-copy region of 89, 144 bp and a small single-copy region of 18, 216 bp. It contained 113 different genes, including 79 protein-coding genes, 30 transfer RNA (tRNA), and four ribosomal RNA genes. Moreover, we also identified 82 SSRs. The phylogenetic inference based on the whole chloroplast genome of 20 taxa showed P. hancei was sister to P. kadsura .